The impact of non-scheduled news on S&P/ASX50 stocks - Smales, Lee (Financial Services Institute of Australasia (Finsia), 2014)
With the large increase in the availability of news, growing numbers of financial market participants are relying on analytics software to evaluate news events. This paper explores whether indicators processed by analytics software are effective in assigning sentiment, and whether it is possible totrade profitably using such measures. Based on a sample of 33 highly liquid S&P/ASX 50 stocks, the results indicate that while the sentiment indicators correctly classify news, it is unlikely that trading strategies with time horizons of 30 seconds or more (and even moderate transaction costs) will produce statistically significant abnormal returns.